2017
DOI: 10.1016/j.jid.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Mesenchymal Stem Cells Expressing Thioredoxin 1 Attenuate Bleomycin-Induced Skin Fibrosis and Oxidative Stress in Scleroderma

Abstract: Systemic sclerosis (SSc) is an autoimmune disorder that affects multiple organs. It is characterized by a thickening of the dermis and connective tissue caused by collagen accumulation, and vascular injuries that induce hypoxia. The present study investigated the therapeutic potential of bone marrow-derived mesenchymal stem cells (BMSCs) expressing thioredoxin 1 (Trx-1) in treating SSc-mediated skin disease after transplantation into a bleomycin-induced murine model. Mice with bleomycin-induced SSc were subcut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
(22 reference statements)
1
22
0
Order By: Relevance
“…Increased ROS production in the skin causes oxidative stress, which can lead to apoptosis. It has been reported that oxidative stress-induced apoptotic cells were increased in the bleomycininduced fibrotic skin, and transplantation of mesenchymal stem cells overexpressing Trx-1 significantly inhibited oxidative stress and dermal fibrosis induced by bleomycin [44]. In addition, SSc fibroblasts were extremely sensitive to oxidative stress-induced apoptosis [39].…”
Section: Discussionmentioning
confidence: 98%
“…Increased ROS production in the skin causes oxidative stress, which can lead to apoptosis. It has been reported that oxidative stress-induced apoptotic cells were increased in the bleomycininduced fibrotic skin, and transplantation of mesenchymal stem cells overexpressing Trx-1 significantly inhibited oxidative stress and dermal fibrosis induced by bleomycin [44]. In addition, SSc fibroblasts were extremely sensitive to oxidative stress-induced apoptosis [39].…”
Section: Discussionmentioning
confidence: 98%
“…286 Trx inhibits bleomycininduced skin fibrosis by down-regulating TGF-β. 287 Trx overexpression inhibits airway remodelling by inhibiting TGF-β1 and EGFR. 288 Regulating cAMP cAMP plays a protective role in COPD inflammation through its effector proteins EPAC and PKA.…”
Section: Trx and Its Effect In Copdmentioning
confidence: 99%
“…Similarly, human UC-MSCs over-expressing angiotensin-converting enzyme 2 (ACE2) were more efficient than naïve UC-MSCs to decrease collagen content, fibrotic, and pro-inflammatory factors while increasing anti-oxidative and anti-inflammatory mediators (56). Thioredoxin 1 (Trx-1)-overexpressing BM-MSCs were also shown to inhibit apoptosis and fibrosis under hypoxic conditions and to promote the formation of tubular-like structures by endothelial cells in bleomycin-induced lung injury (57). Indeed, strategies for enhancing MSCs survival and/or efficiency have been demonstrated to be of interest in preclinical models of SSc.…”
Section: Mechanisms Of Action Of Msc-based Therapy In Sscmentioning
confidence: 99%